DEONTOLOGY AND ETHICS –SOME DETAILS ON THE VIOLATIONS OF RULES IN SCIENTIFIC RESEARCH ACTIVITY AND THEIR SANCTIONING - Corina DABIJA (BARDĂ) (Challenges of the Knowledge Society)
This study concentrates on ethics and deontology rules which apply in the scientific research activity and has the aim to outline the main violations encountered in practice and their correlative sanctions. The topic is treated both from a philosophical perspective and from a legal point of view, linking ethical theories with real situations. This analysis illustrates our vision regarding the terminology of academic ethics and also presents the main legal, international and national instruments in this respect. Research findings are presented taking into account the more complex framework of collective morality and highlight the causes for which people are tempted to circumvent imposed requirements.